2019
DOI: 10.1186/s13048-019-0575-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of TET3 predicts unfavorable prognosis in patients with ovarian cancer-a bioinformatics integrative analysis

Abstract: Ovarian carcinoma is a lethal gynecological malignancy. Women with ovarian cancer (OC) are highly recurrent and typically diagnosed at late stage. Ten-eleven translocation protein 3 (TET3) belongs to the family of ten-eleven translocations (TETs) which induce DNA demethylation and gene regulation in epigenetic level by converting 5-methylcytosine (5mC) to 5-hydroxymethylcytosine (5hmC). Previous studies indicated that TET3 is overexpressed in ovarian cancer tissues. However, the clinic-pathological functions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 42 publications
1
32
0
1
Order By: Relevance
“…Likewise, we have compared gene expressions among COAD, adjacent normal colon and healthy colon; or lung cancer, adjacent normal lung and healthy lung. 10 As previously reported, 10 , 20 data were normalized in R environment using NormalizeBetweenArrays.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, we have compared gene expressions among COAD, adjacent normal colon and healthy colon; or lung cancer, adjacent normal lung and healthy lung. 10 As previously reported, 10 , 20 data were normalized in R environment using NormalizeBetweenArrays.…”
Section: Methodsmentioning
confidence: 99%
“…It was used to compare ACE2 expression between cancer and normal tissues. In addition, we downloaded the data of number of fragments per kilobase of exon per million reads (FPKM) in cancer, adjacent normal tissue and healthy tissue from TCGA or GTEx, which were normalized in R environment using NormalizeBetweenArrays [24]. In addition, pairwise comparisons of ACE2 expression were performed in TCGA datasets.…”
Section: Comparisons Of Ace2 Expression Among Cancer Adjacent Normalmentioning
confidence: 99%
“…Furthermore, increasing evidence suggests a close association between TET3 and PD‐L1 in cancers. Cao et al [ 24 ] demonstrated that the elevated expression of TET3 is associated with poor clinic‐pathological functions and poor prognosis for ovarian cancer. More importantly, the active demethylation of PD‐L1 promoter was concomitant with the upregulation of TET3 in human breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%